CHARACTERISTIC OF PROFESSIONAL AND TEACHING ACTIVITY OF THE TECHNICAL DISCIPLINES’ EDUCATOR IN A VOCATIONAL EDUCATION INSTITUTION - Koeberlein-Kerler, Juergen (Problems of Engineer-Pedagogical Education, 2020)
The Article discusses the professional and teaching activity of educators in the vocational education institutions. On the basis of regulatory documents, a list of positions of teaching employees in the vocational education institutions is defined, which allow teaching employees to teach the disciplines of theoretical education: teacher of vocational education and educator in a vocational education institution. The qualification requirements for the above-mentioned positions of teaching employees were analyzed; their tasks and functions were defined, as well as requirements for educational level were determined. A more specific direction of professional and teaching activity of an educator in a vocational education institution and a teacher of vocational education was established, and the concept of "technical disciplines’ educator" was introduced (a teaching employee who teaches disciplines the subject of study of which is technology and technological processes). The article defines the versatile abilities of a technical disciplines’ educator necessary for successful carrying out of professional and teaching activity. The definitions of the terms "teaching" and "professional and teaching" activity are compared. The professional and teaching activity of an educator of technical disciplines in a vocational education institution was characterized. On the basis of the analysis of the scientific and teaching literature, the types of professional and teaching activity of the technical disciplines’ educator in the vocational education institution are determined in accordance with the subject of activity, and components of activity are determined in accordance with the features of activity. The correspondence between the tasks and functions of the educator of technical disciplines is established, as well as the types and components of activity are determined. It has been determined that the fulfillment of certain tasks and responsibilities of a technical disciplines’ educator can occur both in the context of a specific type or component of activity and several ones, which is related to the integrated nature of the professional and teaching activity.